Analysis of Marriage Without a Guardian for Former Foreign Migrant Workers from Aikmel District, East Lombok, from the Perspective of Maqashid Syariah - Ahmad hulaifi; Mirwan, Mirwan (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the phenomenon of marriage without a guardian among former Indonesian migrant workers (TKI) from Aikmel District, East Lombok, in their respective countries. The research method used was qualitative with a sociological approach. Data were collected through in-depth interviews, focus group discussions (FGDs), and documentation studies with 20 respondents. The research results show that the practice of marriage without a guardian has various typologies, ranging from women marrying themselves, using taklik guardians, guardians of local judges (KUA), to guardians with unclear status. The reasons behind these marriages vary, such as seeking protection, avoiding adultery, gaining peace of mind and offspring, and—in some cases—because of a desire to avenge disappointment and freedom of action. Analysis from the perspective of Maqasid Syariah concludes that some reasons for marriage without a guardian, such as protecting the soul, offspring, and honor (hifzh an-nafs, an-nasl, al-'irdl), are in line with the objectives of sharia. However, reasons based on revenge and the desire for absolute freedom without consideration of sharia are considered outside the maqasid of marriage in Islam, even though they may be considered valid from a fiqh perspective by some schools of thought.